2016
DOI: 10.4236/epe.2016.811030
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Optimum Insulation Thickness of External Walls to Energy Saving and Emissions of CO<sub>2</sub> and SO<sub>2</sub> for Turkey Different Climate Regions

Abstract: In this study, the optimum insulation thickness of the external walls of the housing and it's energy saving and environmental impact in the provinces-Ardahan, Aydın, Eskişehir and Samsun-located in four different climate regions of Turkey was calculated for the expanded polystyrene and polyurethane insulation materials. Natural gas and coal were selected as fuels. Ardahan in the coldest climate region and Aydın in the hottest climate region, for the coal and optimum thickness of expanded polystyrene and polyur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 35 publications
1
3
0
2
Order By: Relevance
“…Toplam maliyet ( , $/m 2 ) ve net enerji tasarrufu ( , $/m 2 yıl) şu şekilde hesaplanabilir [1,9]:…”
Section: İzolasyon Kalınlığı Ve Ekonomik Analizunclassified
See 1 more Smart Citation
“…Toplam maliyet ( , $/m 2 ) ve net enerji tasarrufu ( , $/m 2 yıl) şu şekilde hesaplanabilir [1,9]:…”
Section: İzolasyon Kalınlığı Ve Ekonomik Analizunclassified
“…Artan talebi karşılamanın en kolay yollarından biri fosil yakıt kaynaklarını kullanmaktır. Bununla birlikte, fosil yakıtların sınırlı miktarı, enerji fiyatının artması, çevre sorunları ve küresel ısınma gibi nedenlerle enerjinin etkin kullanımı önemli hale gelmiştir [1], [2]. Ülkemizde birincil enerji kaynakları tüketiminde petrol, 2008 yılına kadar ilk sırada yer alırken, artık yerini doğal gaza bırakmıştır.…”
Section: Introductionunclassified
“…For example, in Malatya [10], Denizli [15,18,22], Erzurum [17], İstanbul [20], Bilecik [23], Bursa [24], İzmir and Ankara [25], Diyarbakır [26]. Moreover, some studies are carried out by selecting only one [27][28][29][30][31][32][33][34][35][36] or more [11][12][13][37][38][39] cities from each climatic zone; furthermore, by merely opting for cold towns [9,14] in Turkey. In most of them, different parameters (types of bricks, insulation materials, and fuels) are investigated by economic and environmental analysis to find the ideal configuration.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Dombaycı [18] investigated the environmental impact of optimum insulation layer thickness for the best insulation material (expanded polystyrene) and fuel type (coal) and found that the reduction in CO 2 emission is 41.5%. Then, Dombaycı et al [32] examined the optimum insulation layer thickness with economic and environmental analysis for Aydın, Samsun, Eskişehir, Ardahan, which are located in four different climate zones of Turkey. The authors selected expanded polystyrene and polyurethane as insulation materials, coal and natural gas as fuel types.…”
Section: Introductionmentioning
confidence: 99%
“…The definition of OIT has been detailed by many researchers worldwide [8][9][10]. The degree-day (DD) method is commonly used to calculate the energy needs of buildings, and methods of calculating the OIT are proposed based on the DD method [11][12][13].…”
Section: Introductionmentioning
confidence: 99%